The Christmas list - Evans, Richard Paul. (New York : Simon & Schuster, 2009)
A holiday novel of hope, love, and redemption in which a husband is given the opportunity to confront his own legacy.
Keywords: Life change events -- Fiction; Redemption -- Fiction; Christmas stories